The Translation of Yemeni –Arabic legal documents into English: Problems and Suggestions - Khoshafah, Hakima Mansour Ahmed (Arab Journal for Sciences and Research Publishing, 2023)
This research shed light on the translating Yemeni legal documents from Arabic to English. It has a two-fold goal: 1) to identify the problems which Yemeni professional translators encounter in translating legal documents, and; 2) to suggest some remedial procedures to help Yemeni translators overcome their weaknesses. This research was designed to study the legal translation problems in Yemeni documents, analyzing them comprehensively and qualitatively, and therefore quantitively data and statistics were not used in the research process. Several methodological procedures are followed; firstly, ten different Yemeni-Arabic legal documents selected. Secondly, a random sample consisting of ten licensed Yemeni translators selected. Thirdly; a thorough analysis of the returned English translations carried out and assessed against suggested translations, based on three main sources: 1) typical translations of the same done by renowned authors or translators; 2) entries in Arabic-English legal dictionaries; and 3) the researcher’s expertise in this field; Fourthly; the results of the study discussed. The findings indicated that the translation of Yemeni-Arabic legal documents is highly problematic. The study concluded with some suggestions and recommendations.